Cascading Hazards in a Migrating Forearc‐Arc System: Earthquake and Eruption Triggering in Nicaragua. Issue 12 (23rd December 2022) - Higgins, M.; La Femina, P. C.; Saballos, A. J.; Ouertani, S.; Fischer, K. M.; Geirsson, H.; Strauch, W.; Mattioli, G.; Malservisi, R.
Abstract: Strain partitioning in oblique convergent margins results in margin‐parallel shear in the overriding plate. Margin‐parallel shear is often accommodated by margin‐parallel strike‐slip faults proximal to active volcanic arcs. Along the Nicaraguan segment of the Central American Forearc (CAFA) in the Cocos‐Caribbean plate convergent margin, there are no well‐expressed right‐lateral faults that accommodate CA‐CAFA relative motion. Instead, historical earthquakes and mapped fault orientations indicate that the ∼12 mm/yr of dextral motion is accommodated on arc‐normal, left‐lateral faults (i.e., bookshelf faults). We investigate three upper‐plate earthquakes; the 10 April 2014 ( M w 6.1), 15 September 2016 ( M w 5.7), and 28 September 2016 ( M w 5.5), using Global Position System co‐seismic displacements and relocated earthquake aftershocks. Our analyses of the three earthquakes indicate that the 10 April 2014 earthquake ruptured an unmapped margin‐parallel right‐lateral fault in Lago Xolotlán (Managua) and the September 2016 earthquakes ruptured arc‐normal, left‐lateral and oblique‐slip faults. These earthquakes represent a triggered sequence whereby the 10 April 2014 earthquake promoted failure of the faults that ruptured in September 2016 by imparting a static Coulomb stress change (ΔCFS) of 0.02–0.07 MPa. Likewise, the 15 September 2016, earthquake additionally promoted failure (ΔCFS of 0.08–0.1 MPa) on sub‐parallel faults that ruptured in two subsequent earthquakes. We also present an instance of magma‐tectonic interaction whereby the 10 April 2014 earthquake dilated (10s of μStrain) the shallow magmatic system of Momotombo Volcano, which led to magma injection, ascent, and eruption on 1 December 2015, after ∼100 years of quiescence. Plain Language Summary: The tectonic boundary between the northwest migrating Central American Forearc (CAFA), located between the active Central American Volcanic Arc and the Middle America Trench, and the CA plate poses significant seismic and volcanic hazards. Shallow, damaging earthquakes occur along the boundary and within close proximity to volcanic centers. We present models of GPS‐derived co‐seismic displacements and relocated seismicity that indicate these earthquakes primarily occur on faults perpendicular to the forearc, unlike most global analogs where motion is accommodated by faults parallel to the margin. Our analysis of these earthquakes also shows that they are a triggered sequence, where each earthquake primed nearby faults for failure, resulting in subsequent earthquakes. The triggered earthquake sequence has implications for seismicity migrating through the forearc and short‐ (years) to medium‐term (decadal) seismic forecasting. We also found that one of the earthquakes perturbed the Momotombo Volcano magmatic system thereby allowing the movement of magma, which lead to an eruption. Key Points: Three upper‐plate earthquakes show Central American Forearc‐CA plate motion is primarily accommodated by left‐lateral arc‐normal faults The three upper‐plate earthquakes were a triggered sequence, indicating stress migration through the arc The 10 April 2014 earthquake dilated the Momotombo magma system, allowing magma injection and ascent, leading to the 2015 eruption